Pendampingan Membaca Kitab Kuning Berbahasa Melayu Sebagai Motivasi Meningkatkan Religiusitas Siswa Di SMAN 2 Palangka Raya - Haryanto, Rizki; Surawan, Surawan; Rohmah, Cindy Dwi (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2025)
The purpose of the training activity is to improve the religiosity of students by facilitating access to the yellow book which is presented in Malay so that it is easier for students to read it. This service method uses the Service Learning method which is a form of learning process strategy that integrates benefits for the community through appropriate learning and evaluation, provides many learning experiences, builds a sense of responsibility, and strengthens the community. The activities were carried out on 4 and 18 September 2024 at 15.00-17.00 WIB, and on 2 and 16 October 2024 at 15.00-17.00 WIB. The results of the training activities showed a significant increase in students' ability to read the yellow book in Malay through structured methods and motivation to add insight into religious knowledge individually. This training not only provides benefits in the intellectual aspect, but also plays an important role in the formation of students' religious character